Autonomic Reactivity to Infant Crying in Maltreating Mothers. (May 2014) - Reijman, Sophie; Alink, Lenneke R. A.; Block, Laura H. C. G. Compier-de; Werner, Claudia D.; Maras, Athanasios; Rijnberk, Corine; IJzendoorn, Marinus H. van; Bakermans-Kranenburg, Marian J.
We examined autonomic reactivity to infant crying in a sample of 42 maltreating and 38 non-maltreating mothers. Exploratively, we tested if differential reactivity was related to child neglect versus the combination of neglect and abuse, and we tested whether mothers' experiences with maltreatment in their own childhood moderated the association between their current maltreatment status and physiology. During a standardized cry paradigm, mothers listened to cry sounds of various pitches. Heart rate (HR), pre-ejection period (PEP), skin conductance levels (SCLs), and vagal tone (root mean square of successive differences [RMSSD]) were measured as indicators of underlying sympathetic and parasympathetic reactivity. The maltreating mothers showed lower SCL reactivity to the cry sounds than non-maltreating mothers. Furthermore, significant negative correlations between HR and PEP in the non-maltreating group differed from nonsignificant correlations in the maltreating group, which suggests a lack of sympathetic cardiac control in maltreating mothers. We found no differences between neglectful mothers and those who were additionally abusive. Together, our findings support the notion of sympathetic hypoarousal as a risk factor for child maltreatment, which may be indicative of disengagement in a caregiving context. Intervention programs might focus on improving maternal sensitivity to improve responsiveness to child signals.